Partisipasi Mahasiswa dalam Gotong Royong untuk Kebersihan Lingkungan di Sekitar Kampus - Pakpahan, Novritsar Hasitongan; Ilmi, Ichyaul; Negara, Dharma Setiawan; Hardyansah, Rommy; Dirgantara, Febrian (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
This community service activity was carried out to explore and encourage increased involvement of students, local communities, and the government in collective efforts to maintain environmental cleanliness, particularly in areas surrounding the campus. Gotong royong is an important tradition in Indonesia that plays a significant role in preserving environmental cleanliness and public health. However, its implementation is often influenced by various factors that affect the success and sustainability of cleanliness programs. This activity applied the Participatory Action Research (PAR) method as an approach that promotes the active participation of students, communities, and the government at all stages of the program, starting from planning and implementation to evaluation. The results of the activity indicate a significant increase in student and community participation in gotong royong activities. This improvement was influenced by several factors, including greater awareness of the importance of environmental cleanliness, support from the community, support from the local government, and the availability of adequate facilities. Therefore, it can be concluded that students’ contributions in promoting environmental cleanliness and sustainability have a real and significant impact. In addition to positively affecting environmental conditions around the campus, this activity also plays a role in shaping students’ character and fostering a sense of environmental responsibility.